Identifying gaps in HIV service delivery across the diagnosis‐to‐treatment cascade: findings from health facility surveys in six sub‐Saharan countries. Issue 1 (1st January 2017) - Church, Kathryn; Machiyama, Kazuyo; Todd, Jim; Njamwea, Brian; Mwangome, Mary; Hosegood, Vicky; Michel, Janet; Oti, Samuel; Nyamukapa, Constance; Crampin, Amelia; Amek, Nyaguara; Nakigozi, Gertrude; et al.
Abstract: Introduction: Despite the rollout of antiretroviral therapy (ART), challenges remain in ensuring timely access to care and treatment for people living with HIV. As part of a multi‐country study to investigate HIV mortality, we conducted health facility surveys within 10 health and demographic surveillance system sites across six countries in Eastern and Southern Africa to investigate clinic‐level factors influencing (i) use of HIV testing services, (ii) use of HIV care and treatment and (iii) patient retention on ART. Methods: Health facilities ( n  = 156) were sampled within 10 surveillance sites: Nairobi and Kisumu (Kenya), Karonga (Malawi), Agincourt and uMkhanyakude (South Africa), Ifakara and Kisesa (Tanzania), Kyamulibwa and Rakai (Uganda) and Manicaland (Zimbabwe). Structured questionnaires were administered to in‐charge staff members of HIV testing, prevention of mother‐to‐child transmission (PMTCT) and ART units within the facilities. Forty‐one indicators influencing uptake and patient retention along the continuum of HIV care were compared across sites using descriptive statistics. Results: The number of facilities surveyed ranged from six in Malawi to 36 in Zimbabwe. Eighty percent were government‐run; 73% were lower‐level facilities and 17% were district/referral hospitals. Client load varied widely, from less than one up to 65 HIV testing clients per provider per week. Most facilities (>80%) delivered services or interventions that would support patient retention in care such as delivering free services, offering PMTCT within antenatal care, pre‐ART monitoring and adherence counselling. Many facilities under‐delivered in several areas, however, such as targeted testing for high‐risk groups (21%) and mobile testing (36%). There were also intra‐site and inter‐site differences, including in the delivery of Option B+ (ranging from 6% in Kisumu to 93% in Kyamulibwa), and nurse‐led ART initiation (ranging from 50% in Kisesa to 100% in Karonga and Agincourt). Only facilities in Malawi did not require additional lab tests for ART initiation. Stock‐outs of HIV test kits and antiretroviral drugs were particularly common in Tanzania. Conclusions: We identified a high standard of health facility performance in delivering strategies that may support progression through the continuum of HIV care. HIV testing policy and practice was particularly weak. Inter‐ and intra‐country differences in quality and coverage represent opportunities to improve the delivery of comprehensive services to people living with HIV.